2013
DOI: 10.1007/s11011-013-9441-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-chronic effects of purified cathinone from khat (Catha edulis) on behavioural profiles in vervet monkeys (Chlorocebus aethiops)

Abstract: We investigated the cumulative effects of cathinone on behavioural alterations in single-caged vervet monkeys. Fourteen adult vervets were divided into tests (12 animals) and controls (2 animals), and exposed to escalating doses of cathinone at alternate days of each week for 4 months in presence and absence of cage enrichment. One month of pre-treatment phase served to establish baseline values. Composite behavioural scores of aggression, anxiety, abnormal responses, withdrawal and appetite loss were done. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
4
10
0
Order By: Relevance
“…These findings concur with those of Islam et al (1990), who reported a reduction By contrast, others reported that khat induces up-regulation of plasma testosterone in olive baboons (Mwenda et al, 2006). In addition, Nyongesa (2013) mentioned that testosterone increased with lower doses and peaked with medium dose then decreased with high dose of Khat in monkey. Abdulwaheb et al (2007) concluded that Khat has an aphorizing effect at a low dose, while it inhibits sexual behaviour at higher doses.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These findings concur with those of Islam et al (1990), who reported a reduction By contrast, others reported that khat induces up-regulation of plasma testosterone in olive baboons (Mwenda et al, 2006). In addition, Nyongesa (2013) mentioned that testosterone increased with lower doses and peaked with medium dose then decreased with high dose of Khat in monkey. Abdulwaheb et al (2007) concluded that Khat has an aphorizing effect at a low dose, while it inhibits sexual behaviour at higher doses.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the adverse effects of tannins from forages include reduced palatability, low rate of evacuation of digesta out of the rumen (stomach), gastritis and other toxic effects (Silanikove et al, 1996). (Nyongesa, 2013). As revealed in the present study, the treated groups that administered higher doses of Khat extract (groups II and III) recorded a significantly lower serum testosterone level compared with control animals.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…However, an underestimate is equally possible; most studies use racemic mixtures of cathinone, rather than the naturally occurring enantiomer, which is several times more potent (Sulzer et al., 2005). Furthermore, chronic drug use is difficult to mimic because animal studies are carried out within a short time frame (Nyongesa et al., 2013).…”
Section: Dependencementioning
confidence: 99%